The effects of Biomin Product A and vomitoxin on growth performance of nursery pigs - H L Frobose; K Soltwedel; Michael D Tokach; Joel M DeRouchey; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 340 barrows (PIC 1050, initially 25.7 lb ± 0.2 lb BW and 35 d of age) were used in a 28-d growth trial examining the effects on nursery pig growth performance of adding Biomin Product A (Biomin; Herzogenburg, Austria) to diets contaminated with deoxynivalenol (DON), or vomitoxin on nursery pig growth performance. Also, 5% water was added in a diet with Biomin Product A as a means of potentially enhancing the activity of the product. Pigs were allotted to pens by weight, and pens were assigned to 1 of 8 treatments in a randomized complete block design with location in the barn serving as the blocking factor. There were 9 replications per treatment (pens) and 4 to 5 pigs per pen. Initial mycotoxin analyses were conducted on the primary ingredients at Romer Labs5 and served as the basis of diet formulation. Eight dietary treatments were formulated to contain: (1) no vomitoxin or Biomin Product A, (2) 1.5 ppm vomitoxin and no Biomin Product A, (3) 1.5 ppm vomitoxin and 0.15% Biomin Product A (3 lb/ton), (4) 1.5 ppm vomitoxin and 0.30% Biomin Product A (6 lb/ton), (5) 3.0 ppm vomitoxin and no Biomin Product A, (6) 3.0 ppm vomitoxin and 0.30% Biomin Product A (6 lb/ton), (7) 3.0 ppm and 0.45% Biomin Product A (9 lb/ton), and (8) 3.0 ppm vomitoxin and 0.45% Biomin Product A with 5% water added to the diet. Dried distillers grains with solubles containing vomitoxin were used to increase concentrations in the treatment diets. After feed manufacturing, ingredients and diets were analyzed at Romer Labs and NDSU6. DON levels for the low- (1.5 ppm) and high- (3.0 ppm) vomitoxin diets were determined to average 2.5 and 5.2 ppm, respectively. Experimental diets were fed in meal form from d 0 to 21, and a common diet was fed from d 21 to 28 to evaluate performance immediately after removing vomitoxin from the diet. Overall (d 0 to 21), pigs fed high-vomitoxin diets had decreased (P<0.01) ADG and ADFI compared to pigs fed diets lower in DON concentration. Adding Biomin Product A to diets containing vomitoxin had no effect (P>0.24) on ADG; however, adding Biomin Product A to low-vomitoxin diets increased (quadratic, P<0.01) ADFI, resulting in poorer (quadratic, P<0.01) F/G. Furthermore, there were no differences (P>0.39) in performance or feed efficiency when 5% water was added to the diet containing Biomin Product A. In conclusion, adding Biomin Product A to the diet did not improve nursery pig performance during the 3-week period during which diets containing low or high concentrations of vomitoxin were fed.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Nursery pig; Vomitoxin